BizTalk 2013 EDI for Supply Chain Management Working with Invoices, Purchase Orders and Related Document Types - Beckner, Mark.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Building a successful supply chain processing EDI implementation in BizTalk Server can be complex. Decisions must be made around how to extract and publish data, how to map to the various EDI standards, and how to appropriately batch and deliver data. If architected properly, your BizTalk solution can be highly efficient, simple, and something that can be managed and extended for years to come. The topics in this book include building complete inbound and outbound solutions for 810, 845, and 850 EDI document types, which will lay the groundwork for any document type you may be implementing. In addition, topics on how to set up FTP, SFTP, and AS2 protocols for document exchange, working with 997/999 acknowledgements, and creating custom applications for archiving and monitoring data are included. Covering mapping, architectural patterns, orchestrations, trading partner configurations, AS2, SFTP, FTP, usage of role links, and data routing, you will find that BizTalk 2013 EDI for Supply Chain Management gives you the detail and knowledge needed for success with your own implementations.
Keywords: Computer science; Information systems; Computer Science; Information Systems and Communication Service